A RARE EARTH ELEMENT-RICH CARBONATITE DYKE AT BAYAN OBO, INNER MONGOLIA, NORTH CHINA - Yang X.-M.; Yang X.-Y.; Zheng Y.-F.; Le Bas M.J. (My University, 2003)
A carbonatite dyke, extremely enriched in rare earth elements (REE), is reported from Bayan Obo, Inner Mongolia, North China. The REE content in the dyke varies from 1 wt% to up to 20 wt%. The light REEs are enriched and highly fractionated relative to the heavy REEs, and there is no Eu anomaly. Although carbon isotope δ13C (PDB) values of the carbonatites (−7.3 to −4.7‰) are within the range of normal mantle (−5±2‰), oxygen isotope δ18O (SMOW) (11.9 to 17.7‰) ratios apparently are higher than those of the mantle (5.7±1.0‰), indicating varying degrees of exchange with hydrothermal fluids during or after magmatic crystallization. The carbonatite is the result of partial melting followed by fractional crystallization. Primary carbonatite melt was formed by less than 1% partial melting of enriched mantle, leaving a garnet-bearing residue. The melt then rose to a crustal magma chamber and underwent fractional crystallization, producing further REE enrichment. The REE and trace element distribution patterns of the carbonatites are similar to those of fine-grained dolomite marble, the ore-host rock of the Bayan Obo REE–Nb–Fe giant mineral deposit. This fact may indicate a petrogenetic link between the dykes described here and the Bayan Obo mineral deposit.